Human Resource Management at Russian Companies — Leaders of the Global Economy - Elena Zavyalova; Dmitry Kucherov; Victoria Tsybova (Foresight and STI Governance, 2017)
One of the main sources of competitiveness on the modern economy are the  intangible assets of companies. In the structure of the intellectual capital assigned to human resources and human capital,  the knowledge, skills, creativity, and employees’ motivation play a special role. The quality of human resources affects the value of the company and human resource management practices, which in turn affect the quality of its human resources.